2019
DOI: 10.33899/magrj.2019.163282
|View full text |Cite
|
Sign up to set email alerts
|

Status and Distribution of Different Potassium Forms in Calcareous Soils in Northern Iraq

Abstract: 1n the last few years, the demand increased especially in the developing countries for food production. One of the parameters to increase the production quantitatively and qualitatively is the use of fertilizers by following the modern techniques in fertilization which needs a detail soil studies. This study highlighted on behavior of different forms of potassium, their distributions through soil profile, and the relationships between them and with soil other properties. To represent a detailed study of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
5
1
0
Order By: Relevance
“…In the table (4) shown that exchangeable K had highly significant correlation with available K, non-exchangeable-K and silt content with the correlation coefficient values or r = 0.96**, r= 0.75**, and r= 0.80** respectively and significant positive correlated with total-K (0.067*) and negatively correlated but nonsignificant with CEC (-0.44). Without CEC, these results are agreeing with the results found by AL-Badrani and Radhwan (2019). The exchangeable potassium is more related to the type and amount of clay and its net negative charge (Parfitt, 1992).…”
Section: -Exchangeable Potassiumsupporting
confidence: 90%
See 4 more Smart Citations
“…In the table (4) shown that exchangeable K had highly significant correlation with available K, non-exchangeable-K and silt content with the correlation coefficient values or r = 0.96**, r= 0.75**, and r= 0.80** respectively and significant positive correlated with total-K (0.067*) and negatively correlated but nonsignificant with CEC (-0.44). Without CEC, these results are agreeing with the results found by AL-Badrani and Radhwan (2019). The exchangeable potassium is more related to the type and amount of clay and its net negative charge (Parfitt, 1992).…”
Section: -Exchangeable Potassiumsupporting
confidence: 90%
“…Table (4) illustrates a significant and positive relationship between available potassium with non-exchangeable-K (r=0.71**), total-K (r=0.67*) silt (r=0.80**) while negative nonsignificant correlation observed to CEC (-0.46). These results are similar to those noted by (Saini and Grewal, 2014;AL-Badrani and Radhwan, 2019). The positive correlations between forms of potassium with other forms point out that the available-K is governed by the other forms of potassium in the soil.…”
Section: -Available Potassiumsupporting
confidence: 89%
See 3 more Smart Citations